The Link of the Monetary Indicator to Future Inflation in the Euro-Area: A Simulation Experiment - Jan Gottschalk; Stéphanie Stolz (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
We examine the indicator property of the monetary indicator for inflation. Using a P*-model, Svensson (2000) shows theoretically that the relationship between these two variables is rather tenuous. The present study employs empirical evidence on the relations in his model to quantify its dynamics for the Euro-area. Moreover, we extend Svensson's analysis by considering different shocks and monetary regimes. It becomes apparent that the system exhibits complicated dynamics and that for most shocks and policy regimes the monetary indicator is not a leading indicator of dangers to price stability at the medium-term. – – Der Artikel untersucht die Indikatoreigenschaften der Geldmenge für die Inflation. Unter Verwendung eines P*-Modells hat Svensson (2000) theoretisch gezeigt, dass die Beziehung zwischen beiden Größen recht schwach ausgeprägt ist. Die vorliegende Studie präsentiert empirische Evidenz für die Beziehung im Euroraum. Dabei wird Svenssons Ansatz durch die Berücksichtigung verschiedener Schocks sowie unter schiedlicher monetärer Regime erweitert. Es wird gezeigt, dass in den meisten Fällen das System eine komplizierte Dynamik aufweist und die Geldmenge mittelfristig kein Frühindikator für die Gefährdung der Preisstabilität ist.
Keywords: 330; Monetärer Indikator; Inflation; Prognoseverfahren; Preisniveau; P-Star; Eurozone; Simulation; Theorie; EU-Staaten